IMPLEMENTATION OF SHODAQOH INFAQ WARGA (SIAGA) PROGRAM IN PRODUCING ULAMA CADRES AT THE BAITUL MAKMUR KEMBANGSONGO MOSQUE BANTUL - Rosyid, Isnan; Bahiroh, Siti; Tago, Mahli Zainuddin; Purnomo, Halim; Fauzan, Aris (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
Not all mosques have activities to produce ulama cadres. The cadre formation of ulama is important for the continuity of da'wah in an area. This research aimed to describe the implementation of Shodaqoh Infaq Warga (SIAGA) to produce ulama cadres at the Baitul Makmur mosque, Bantul, Yogyakarta. This research was descriptive research with a case study. The research informants were the chairman of the mosque takmir, the chairman of the SIAGA division, community leaders, and leaders of Islamic boarding schools who collaborated with the takmir. The research method used is a case study with data collection techniques in the form of interviews, observation and documentation. Data were analyzed qualitatively using Robert K. Yin model. The research results show that SIAGA activities include planning, organizing, coordinating, and controlling, as well as two new stages, maintaining and sustaining. The SIAGA activities have implemented Islamic communication principles in their execution, including qaulān balīghān, qaulān maysūrān, qaulān karīmān, qaulān ma’rūfān, qaulān layyinān and qaulan sadīdān. The SIAGA program is considered effective in producing ulama cadres. The SIAGA activities in Kembangsongo Bantul village have also inspired neighboring villages to initiate similar programs to develop future religious scholars. Evaluation research on SIAGA activities needs to be carried out to analyze their effectiveness.